2008
DOI: 10.1007/s10979-007-9102-z
|View full text |Cite
|
Sign up to set email alerts
|

Do a law's policy implications affect beliefs about its constitutionality? An experimental test.

Abstract: Although a substantial empirical literature has found associations between judges' political orientation and their judicial decisions, the nature of the relationship between policy preferences and constitutional reasoning remains unclear. In this experimental study, law students were asked to determine the constitutionality of a hypothetical law, where the policy implications of the law were manipulated while holding all legal evidence constant. The data indicate that, even with an incentive to select the ruli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In both states, conservative voters tended to vote in favor of anti-minority measures and to oppose judicial review, either in a more general way, or very specifically with respect to a distinct ballot measure. This finding is in line with experimental data provided by Furgeson et al (2008), who show that political preferences influence how voters interpret the constitutionality of a law. As anti-civil-rights initiatives have been closer to conservative preferences over the last 20 years (Miller, 2009, p. 89), conservatives are also more skeptical of judicial review in both the states.…”
Section: Discussionsupporting
confidence: 91%
“…In both states, conservative voters tended to vote in favor of anti-minority measures and to oppose judicial review, either in a more general way, or very specifically with respect to a distinct ballot measure. This finding is in line with experimental data provided by Furgeson et al (2008), who show that political preferences influence how voters interpret the constitutionality of a law. As anti-civil-rights initiatives have been closer to conservative preferences over the last 20 years (Miller, 2009, p. 89), conservatives are also more skeptical of judicial review in both the states.…”
Section: Discussionsupporting
confidence: 91%
“…Using general political ideology (liberal versus conservative) as an independent variable, one study asked law students to determine whether a change in a school district's tax rate violated a state constitutional provision (Furgeson et al 2008). Half the participants were told that the change raised taxes, whereas the other half were told that the change lowered taxes.…”
Section: Liberal-conservativementioning
confidence: 99%
“…Legal training does not necessarily provide inoculation against motivated cognition, as evidenced by several of the experiments that demonstrated this phenomenon in the judgments of law students and/or judges (Braman & Nelson 2007, Furgeson et al 2008, Redding & Reppucci 1999. In fact, in their study on evaluations of legal precedents, Braman & Nelson (2007, p. 952) reported that the motivated cognition effect was actually "stronger and more consistent" in law student participants than in those without legal training.…”
Section: Judicial Decision Makingmentioning
confidence: 99%
“…The latter four articles concern the assessment of legally charged complex facts such as causation or consent, which straddle the boundary between fact and law's application to fact. 3 Holyoak and Simon (1999); Simon et al (2001); Braman and Nelson (2007); Furgeson et al (2008aFurgeson et al ( , 2008b; Wistrich et al (2014); Kahan et al (2015).…”
Section: Introductionmentioning
confidence: 99%